Partial differential equations - Walet, Niels (The University of Hull)
A second year course in the Mathematics of partial differential equations for physics students. Contains lecture notes, examples, ... as well as the files used to create these resources. Discusses: 1 Introduction 2 Classiﬁcation of partial diﬀerential equations. 3 Boundary and initial conditions 4 Fourier series 5 Separation of variables on rectangular domains 6 D’Alembert’s solution to the wave equation 7 Polar and spherical coordinate systems 8 Separation of variables in polar coordinates 9 Series solutions of O.D.E. 10 Bessel functions 11 Separation of variables in three dimensions